Three-Jaw Chuck Pinch Strength and Its Correlation with Hand Breadth in Electronic Technicians - Akter, Shahnawaz; Asha, Moushumi Taher; Ara, Shamim; Kishwara, Segupta; Shahriah, Sunjida (International Journal of Human and Health Sciences (IJHHS), 2022)
Context: The three jaw chuck pinch refers to an act where placing the object between the pad of the distal phalanx of the thumb opposing the pads of the distal phalanges of both the index finger and the middle finger. Pinch strength is generally influenced by the health status and level of physical activity of a person. Objectives: The present study was planned to measure the correlation of three-jaw chuck pinch strength with hand breadth in electronics technicians working in Dhaka Metropolitan City. The data obtained from the study used as a base line for other professions as well as for research in our country. Methods: A cross-sectional, analytical study was carried out in the department of Anatomy, Dhaka Medical College, Dhaka during the period of July’ 2015 to June’ 2016 with 100 adult male electronics technicians and 100 adult sedentary workers. Collection was done by convenient purposive sampling technique. Hand breadth was measured by digital slide calipers and pinch gauge was used to measure the three-jaw chuck pinch strength. Results: The mean three-jaw chuck pinch strength was significantly higher (P<0.05) in case group than in the control group. Significant difference also observed between case group and control group in the mean hand breadth (P<0.05). Mean hand breadth was greater in case group than that of control group. Three-jaw chuck pinch strength showed significant positive correlation with hand breadth in case group. Case group was further subdivided according to their working experiences, the mean three-jaw chuck pinch strength and hand breadth was significantly higher (P<0.05) in more working experience group than in less working experience group. Conclusion: Three-jaw chuck pinch strength showed significant positive correlation with hand breadth. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 108-112